Adaptabilidade, estabilidade e estratificação ambiental em genótipos de milho na região sul do Estado do Tocantins - Dotto, Michel Antônio (Universidade Federal do Tocantins, 2017)
The maize crop presents great socioeconomic importance in Brazil, due to the remarkable variety of products that use it in its composition, as well as the possibility of direct consumption in human food or animal feed. As well as its use corn cultivation occurs in all regions of Brazil, causing great effect of Genotype x environment interaction, generating problems of recommendation and instability in production. To minimize such effects, measures should be taken in order to ensure that the recommendation of the same assertive. In this context, study was performed using six experimental genotypes of maize, developed by the breeding program of the corn crop of Federal University of Tocantins - UFT, Campus of Gurupi and six commercial genotypes, used by producers in the southern region of the state of Tocantins, who served as witnesses, in 24 distinct environments, formed by different levels of nitrogen fertilization in coverage and planting seasons. The experiments were conducted in the UFT, campus of Gurupi, in 2012/13 and 2013/14 harvests. The experimental design consisted of randomized complete blocks, with 12 treatments in three repetitions and plots of two lines of five meters, spaced at 0.75 meters. Ten plants were assessed representative in each plot, followed by tabulation and application of statistical methods. The study was divided into two chapters, being in the first studied the adaptability and stability of genotypes in 24 distinct environments, by the method of Eberhart and Russell (1966), which was effective in classifying the genotypes of broad adaptation, as well as the specific adaptation to favorable environments, unfavorable and the foreseeable behavior. The genotype AL BANDEIRANTE presented more unpredictable behavior and with adaptation specifies the unfavorable environments. The genotypes UFT 2 and BRS GORUTUBA, presented adaptation to favorable environment. The genotypes UFT 5 and BR 205 showed a generally more adapted and responsive to environmental improvement and more stable behavior, being the most indicated for cultivation in the studied environments. In the second chapter, environmental stratification was studied through the method of Lin (1982), who presents efficiently in the classification of environments as similar or divergent and indicated that the different times of planting and nitrogen levels were efficient in the formation of distinct environments in the studied genotypes.